Tumour volume and radiotherapy prolongation in locally advanced head and neck cancer patients treated with radical IMRT - Lohynska, Radka; Jirkovska, Michaela; Malinova, Bela; Novakova-Jiresova, Alena; Pechacova, Zdenka; Kratka, Zuzana (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2022)
AIMS: The relationship of tumour volume, radiotherapy treatment time and other prognostic factors affecting prognosis was evaluated. METHODS: 184 patients with locally advanced head and neck cancer were treated with radical intensity modulated radiotherapy (IMRT) and compared retrospectively. RESULTS: In the multivariate analysis the overall survival was dependent on gross tumour volume (GTV), clinical stage (CS), radiotherapy treatment time (RTT) and p16 status. Local control was influenced by GTV, overall RTT and age. DFS was significantly affected by GTV, CS, RTT, p16 status and concomitant chemotherapy (CHT). CONCLUSIONS: The tumour volume and the radiotherapy treatment time were the most significant prognostic factors with the best outcomes in patients with GTV ≤ 55 cc and RTT ≤ 48 days (mean LC 8.1, DFS 7.1 and OS 6.4 years) and worst outcomes with GTV > 55 cc and RTT >48 days (mean LC 4.4, mean DFS 3.2 and mean OS 2.6 years).
Keywords: head and neck cancer; survival; radioterapie s modulovanou intenzitou; retrospektivní studie; celková dávka radioterapie; prognóza; Radiotherapy, Intensity-Modulated; local control; nádory hlavy a krku; Head and Neck Neoplasms; tumour volume; Tumor Burden; Radiotherapy Dosage; lidé; Humans; Prognosis; tumor burden; Retrospective Studies; radiotherapy treatment time; IMRT